An update on impulse control disorders in Parkinson's disease - Voon, V; Mehta, A (2012)
The impulse control disorders associated with dopaminergic medication in Parkinson's disease provide a clear and unequivocal demonstration of the biological basis of behavioural addiction. These behaviours can be dramatic, resulting in significant financial and social consequences, with functional impairments, and include pathological gambling, compulsive shopping, hypersexuality, binge eating, punding (complex prolonged, purposeless, and stereotyped behaviour) and compulsive medication use. Copyright © 2012 S. Karger AG, Basel.